Ipsilateral Femoral Neck and Shaft Fracture (Journal of Pakistan Orthopaedic Association, 2013)
Background: Fracture of the ipsilateral femoral neck and shaft are not uncommon, but challenging combination of injuries encountered by Orthopedic Surgeons.Objective: Objective of this study was to evaluate the devastating complication of femoral head i.e. avascular necrosis and non union of femoral head and to determine outcome of DHS and cancellous screw fixation for its management.Patients and Methods: This prospective study was conducted in the Department of Orthopedic Surgery Sheikh Zayed Medical College/Hospital from 2008 to 2011. Diaphysial fracture of femur with neck fractures in 24 patients between 16 to 40 years were included in this study. Priority was given to neck fractures which was stabilized as early as patient’s general condition permitted with DHS and Screws and shaft Fracture was fixed with DCP and screws with or without bone grafting. The entire patients were mobilized after surgery on crutches except for patients having other associated injury within one week. Patients were fallowed until 02 years.Results: Union of fracture neck was achieved in 100% of patients treated with DHS and side plate and 78% treated with cannulated screws. Delayed union is 20% and non union 10% of patients treated with cannulated screw. Overall results of union of fracture neck of femur was graded as good union, achieved between 16-28 weeks (83.33%), fair union achieved between 29-46 weeks (8.33%), Poor, Union achieved between 46 weeks (8.33%).Conclusion: The findings of present study in concomitant fractures suggest that DHS with side plate is a good device for management of fracture of neck of femur in concomitant injury as no major complication was detected with this method.